La transformación de las narrativas y proyectos de vida de cubanos/as del oriente de Cuba en Puerto Rico - Ortiz-Torres, Blanca; Rodríguez-Cancel, Mario A. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2019)
Summary This is an exploratory on changes of life projects of cubans from the Eastern region of their country who have migrated to Puerto Rico in the past 20 years. The research intended to: 1) explore how do life projects and narratives are transformed in this group of immigrants; 2) learn about participants’ perception about the differences between them and cubans from other regions; and 3) explore racism and discrimination as experienced by participants. Semi-structured interviews were conducted with 9 participants. The narratives and projects respond primarily to the reasons identified to leave Cuba: economic improvement, professional development and familiy reunification. According to our participants, their projects have now opened to development possibilities and personal and professional aspirations.